Strategi Komunikasi Budaya Mahasiswa Papua dalam Interaksi dengan Mahasiswa Aceh di Universitas Malikussaleh - Mirza Muhajir; Anismar Anismar (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
Intercultural communication is the process by which the ideas of one culture are transferred to another culture. The purpose of this study is to explain the strategy of cultural communication between students from Papua and Aceh students in forming harmonious social interactions at Malikussaleh University. This study uses a descriptive qualitative approach using the theory of William Gudykunts. In obtaining complete and accurate data and information in the study, the data collection used in this study was observation and interviews. The data analysis technique used in this research is data reduction, data presentation, and data inference. The results showed that there were three strata of cultural communication strategies carried out by Papuan students with Acehnese students. First, understand and use good language. Second, understand the norms and character of the interlocutor. Third, positive prejudice against the interlocutor and promote good values.